On the Impossibility of Informationally Efficient Markets: Reply - Stiglitz, Joseph E.; Grossman, Sanford J. (American Economic Review, 1982)
The article presents a reply to the comments of economist Richard Cothren on a paper related to efficient market theory written by the authors. According to the author Cothren's assertion that the authors incorrectly derived an informed trader's risky asset demand function is false. They permitted borrowing and short selling. For this reason there is no nonnegativity constraint on a trader's holdings of risky or risk-free assets. A trader's initial wealth is not the limit on the value of the risky assets that he can purchase. The trader can borrow, and in so doing finance a large purchase of risky assets. The goal of their paper was to show that when information is costly, a perfectly competitive equilibrium will not exist which completely transmits the informed traders' information to uninformed traders. It would have been trivial to prove that constraints on borrowing, or on short sales, prevent perfect arbitrage from occurring. They proved a more interesting result, which is that even in the absence of constraints on borrowing or short sales, markets cannot be fully arbitraged, when information about the arbitrage opportunity is costly.